Dextrose Prolotherapy for Occipital Neuralgia Management - Taufiq Agus Siswagama; Buyung Hartiyo Laksono; Mirza Koeshardiandi (Faculty of Medicine, Brawijaya University, 2021)
Background: Occipital neuralgia defined as a pain such as being stabbed in the skin according to the dermatomes of the greater occipital nerves (GON) and lesser occipital nerves (LON).Case: An 80-year-old male patient diagnosed with occipital neuralgia. Previously, patients were diagnosed with lung cancer six months ago and planned for follow-up chemotherapy. Patient already receive medications including paracetamol, Non-steroidal anti-inflammatory drugs (NSAIDs), minor tranquilizers, and antidepressants, but the pain still exist. Patient then scheduled to receive blocks of GON and LON-ultrasound-guided using plain lidocaine 2% and steroids dexamethasone 10 mg. Fifteen days later, patient receive perineural deep injection along with prolo-hydrodissection in GON and LON using dextrose 15% and local anesthesia lidocaine plain 2% with a volume of 3 cc each nerve. The intervention give a positive outcomes, pain is reduced with NRS rest 0-1, NRS motion 2-3, hearing improves, and the noise in the ear disappears. The patient can sleep using a pillow. Conclusion: Block GON and LON, perineural deep injection along with prolo-hydrodissection provides a positive outcome for occipital neuralgia pain management. This case showed an opportunity for pain specialist to develop pain intervention based on prolotherapy.